The Relationship of Strength of Hip Abductors and Ankle Plantar Flexors with Berg Balance Test in Elderly Women - amin Farzaneh hessari; Solmaz Mahdavi; Masoud Golpaygani (Sport Sciences and Health Research)
The aim of this study was to determine the relationship between the Berg balance test scores and strength of hip abductors and ankle plantar flexors in elderly women. 32 elderly females (mean age: 66.20±5.98 yr, weight: 62.60±5.78 kg, height: 159.94±7.8 cm) voluntary participated in this study. Berg Balance Test (BBT) functions were divided into four categories: 1. Position maintenance, 2. movement within base of support, 3. Movements out of base of support, 4. Movements in and out of base of support. Maximum Voluntary Contraction (MVC) of hip abductor and ankle plantar flexor muscles were measured by Manual Muscle Test (MMT). Pearson correlation coefficient was used to determine the relationship between Berg functions and muscle strength at significance level of 0.05. Results showed a significant relationship between hip abductors and ankle plantar flexors strength and BBT scores in elderly women (P≤0.05). Also, the correlation values between hip abductors and BBT functions (r=0.54-0.62) were higher than plantar flexor strength and BBT functions (r=0.35-0.53). In conclusion, it can be concluded that there were significant relationships between hip abductors and ankle plantar flexors strength and BBT functions and decreased ankle plantar flexors and hip abductors strength was associated with decreased BBT functions